Diurnal Wind Characteristics in and around Chisapani Confluence of Karnali River in Mid-Western Nepal - Maharjan, Sangeeta; Regmi, Ram P. (Journal of Institute of Science and Technology, 2015)
The mountain gap flow characteristics in and around the Chisapani mountain gap of Karnali River basin has been numerically simulated using the Weather Research and Forecasting (WRF) model to understand its spatial and temporal characteristics and its implications. The model was initialized with NCEP initial and boundary conditions to carry continuous integrations 168 long hours to identify the general flow field during early springtime. The river valley accumulates channels and flushes a narrow jet stream of about 10 ms-1 in speed and 500 m in its depth into the vast southern plain via Chisapani mountain gap during night and morning time whereas in the afternoon, the mountain feeds up-valley wind of about 4 ms-1 from the southern plain up into the Karnali River basin. Journal of Institute of Science and Technology, 2015, 20(2): 1-5